PENGEMBANGAN MEDIA PERMAINAN ULAR TANGGA PADA MATERI FILUM ECHINODERMATA UNTUK SISWA KELAS X SMA - Mei Lannie Ayu Putri; Rodiantifitri Nengsih; Rozana Zuhri (BIOCOLONY, 2021)
The research is motivated by there not any of development media for the snake games to explained the material for the phylum echinoderms at SMA N 13 Merangin, the media used were pictures and materials in textbooks. The learning process is still monotonous, the teacher has not developed interesting learning media such as the snake game media. This makes learning less enjoyable, thus pupils are bored and tired during the learning process, fur thermore, they have a low level of interestion learning. To get arownd this, the researchers designed a snake- themed game using material from the echinoderm phylum . This study aims to produce biology learning media in the form of snake games on material for the echinoderm phylum valid and practical in class X SMA. The study is a development study that use a four-stage paradigm that comprises define, design, develop, and disseminate. The purpose of this study is to test the validity of 1 SMA N teacher 13 Merangin and 4 STKIP YPM Bangko lecturers using 5 validators. A questionnaire on the validity of snake games media and a practical questionnaire for instructors were used as study instruments, and the data were then analyzed descriptively. The snake game media product was found to be both legitimate and pratical based on the finding of this analysis. The snake games learning media is declared valid based on validation with 5 validators with revisions and repair. With an average material validation score of 3.16 with a very valid category, language validation 3.66 including a valid intense category, presentation validation 3.70 including a very valid category, and media validation 3.80 including valid intense a category, then overall from each validation get average of 3.57 with a very valid category. The snake game learning media was declared practical based on the results of the practicality test using a teacher's practicality questionnaire. The average is 3.26 with the practical category.